FINANCIAL ANALYSIS AND DEVELOPMENT STRATEGY OF BAYTAT CAKE “ADN” INDUSTRY IN BENGKULU CITY - ANPI SETYAWAN; EVANILA SILVIA; HIDAYAT KOTO (Jurnal Agroindustri, 2018)
The purpose of this research is to determine the potency of “ADN” Baytat cake business, to analyze internal and external analysis of Baytat cake industry and to formulate business strategy to improve competitiveness. Data collection used observation method, interview and questionnaire distribution. Respondents consisted of 10 people consisting of 5 practitioners, 2 from government agencies and 3 from academics. Financial analysis is done descriptively quantitative, to know Total Cost, Net Benefit, B/C Ratio, Break Event Point and Return on Investment. Meanwhile, to design alternative competitiveness strategies using SWOT analysis (Strengths Weaknesses Opportunities Threats). The results showed that: 1) the business potential of “ADN” industry is very profitable and feasible to be developed; 2) based on internal and external environmental analysis, ADN's industry lies in the first quadrant position, and 3) the right strategy to implement is the SO (Strength-Opportunities) strategy that uses the power to exploit opportunities; increase production volume, maintain product quality, Cooperate with government agencies to assist capital and establish good relationships with suppliers as well as supervise the raw materials sent.